Verso una scomposizione della democrazia rappresentativa? : Fra spinte tecnocratiche e pratiche di partecipazione diretta e digitale - Giacomini, Gabriele (Scenari, 2021)
In recent decades long-standing representative democracies seem to be facing a legitimacy crisis. There are essentially two possible diametrically opposite yet inextricably linked reactions to this: adapt institutions to a minor participation or stimulate greater participation. In the first case (e.g. European commission, central banks) we tend to see a technocratic drive, while the second would see a development in direct and digital participation (public policies and participatory budgets, online petitions, platforms for collaborative politics etc.), especially at a local level. Therefore the two components that characterised traditional representative democracy – on the one hand the democracy of the elites, competence, the ruling classes, on the other hand the democracy of the people, participation, mobilisation – are no longer fully integrated in representative democracy as they used to be, but rather juxtapose one another as they move, for example, towards non-majority institutions or the participative experiences of civil society. Representative democracy tends to break up when it is subject to centrifugal forces.